THE ROLE OF FAMILY RELATIONSHIPS IN FORMING THE INITIATIVE OF PRESCHOOL AGE CHILDREN (Universal International Scientific Journal, 2026)
The abstract reveals the impact of a healthy psychological environment in the family, parental upbringing methods, and relationships based on mutual respect and support on the socio-active characteristics of the child's personality. It also notes the importance of approaches aimed at strengthening the family and improving child upbringing within the framework of the activities of the Committee on Family and Women.